1991
DOI: 10.1111/j.1365-2141.1991.tb08062.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemorheological changes in the very short term after abstention from tobacco by cigarette smokers

Abstract: A study was made of the haemorheological changes that took place in the days immediately following tobacco withdrawal from cigarette smokers. In both males and females substantial and persistent reductions in blood viscosity occurred within 2 d, the fall at high shear rate corresponding to about 8% while at low shear rate it was approximately twice as much. These changes were due partly to a fall in packed cell volume (PCV), but also to reductions in total plasma protein and fibrinogen concentrations which led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
(2 reference statements)
1
8
1
2
Order By: Relevance
“…Both the higher plasma fibrinogen concentrations of smokers compared with non-smokers (combined data from Studies 1 and 2), and the significant fall in plasma fibrinogen concentration with 2 weeks abstention from smoking observed in Study 2, are in accordance with previous findings [13,33,34]. Moreover, the elevated levels of plasma fibrinogen concentration in smokers were also significantly correlated with elevated rates of fibrinogen synthesis (Figure 3 ; r l 0.65, P l 0.04).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both the higher plasma fibrinogen concentrations of smokers compared with non-smokers (combined data from Studies 1 and 2), and the significant fall in plasma fibrinogen concentration with 2 weeks abstention from smoking observed in Study 2, are in accordance with previous findings [13,33,34]. Moreover, the elevated levels of plasma fibrinogen concentration in smokers were also significantly correlated with elevated rates of fibrinogen synthesis (Figure 3 ; r l 0.65, P l 0.04).…”
Section: Discussionsupporting
confidence: 91%
“…Ernst et al [11], for example, reported a dose-effect relationship between the number of cigarettes smoked per day and plasma fibrinogen concentration. Conversely, cessation from smoking results in a rapid reduction in plasma fibrinogen [33,34], which subsequently may remain slightly elevated for several years [35]. The present paper aimed to establish if the hyperfibrinogenaemia observed in smokers is accompanied by an increased rate of synthesis and, conversely, whether synthesis is reduced by short-term smoking cessation.…”
Section: Discussionmentioning
confidence: 90%
“…24 Fibrinogen increased more in those who reported starting, continuing, or recently quitting smoking than in consistent nonsmokers, but these findings were statistically nonsignificant due, in part, to the small sample sizes. Other than chance occurrence, we are unclear as to why quitting smoking did not reduce fibrinogen in the present study as it did in short-term clinical trials of smoking cessation 9,25 and the longitudinal study by Meade et al 10 Lifestyle factors not related to fibrinogen change were alcohol change, BMI change, and sports score change. These findings are consistent with those of most clinical trials 9 ; however, Meade et al found longitudinal changes in fibrinogen negatively associated with changes in alcohol consumption.…”
Section: February 2000contrasting
confidence: 51%
“…First of all, cases were distributed to the NST and SST groups almost equally, and none of the patients and accompanying persons were permitted to smoke at least from the time of admission to the time of discharge. It has been reported that following tobacco withdrawal, a rapid (within 2 days), substantial and persistent reduction in plasma fibrinogen occurred [20]. Morten et al [21] concluded in their study that elevated plasma fibrinogen was associated with reduced FEV 1 and an increased risk of COPD, and this was independent from the patient’s smoking habit.…”
Section: Discussionmentioning
confidence: 82%